The Renaissance Group: "The Next Generation" - Giovannetti, Michael (Educational (Re)naissance, 2013)
The “next generation” refers to the generation after the present one. The term is also used in manufacturing, especially for hardware and software, and even Star Trek has a "next generation" of cast members. I am especially attracted to the expression, given it offers a sense of hope and encouragement; although the past and present generations of The Renaissance Group (TRG) have contributed in important ways to supporting and improving educator preparation programs throughout America, the next generation must be more creative in assembling the latest education puzzle and vehemently embrace the expressed and anticipated challenges and opportunities facing P-20 education today, employing the best possible strategies designed to support and strengthened this basic American institution.